2010
DOI: 10.1007/s11136-010-9737-y
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in haematopoietic stem cell transplant survivors: a qualitative study on the role of psychosocial variables and response shifts

Abstract: The response-shift model is a useful theoretical basis for exploring HRQOL in HSCT patients. Response shifts and psychosocial variables may help patients to cope and enabling them to experience good HRQOL despite the negative effects of HSCT. Understanding the adjustment processes has implications for patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 34 publications
1
19
0
1
Order By: Relevance
“…The SCT survivors reported gratifying outcomes such as changed perspectives and positive self‐perception, which are expressions previously reported after childhood cancer . Optimism, changing expectations, goal setting, and social support are some of the psychological and social antecedents and mechanisms that may be helpful to the adjustment to changing health and learning to live with current difficulties posttransplant . In our study, we found that the SCT survivors live rather ordinary lives as measured by socio‐demographic factors despite the intense treatment they have been through.…”
Section: Discussionsupporting
confidence: 69%
“…The SCT survivors reported gratifying outcomes such as changed perspectives and positive self‐perception, which are expressions previously reported after childhood cancer . Optimism, changing expectations, goal setting, and social support are some of the psychological and social antecedents and mechanisms that may be helpful to the adjustment to changing health and learning to live with current difficulties posttransplant . In our study, we found that the SCT survivors live rather ordinary lives as measured by socio‐demographic factors despite the intense treatment they have been through.…”
Section: Discussionsupporting
confidence: 69%
“…However, the effects of personality characteristics on response shift in HRQOL have not been fully investigated. One study found that cancer patients with pessimistic traits may report less improvement in HRQOL than patients with optimistic traits over time despite similar change in underlying health status [124]. Another study using advanced psychometric methods found that cancer patients were susceptible to response shift in general health assessment related to optimism [125].…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction with social support is a wellestablished protective factor and has been linked to lower levels of distress. 28,29 Thus it is important for the staff to educate patient's loved ones and caregivers about this aspect of recovery and to help them maintain levels of adequate support throughout the SCT treatment and recovery process.…”
Section: Discussionmentioning
confidence: 99%